Cognitive neuroscience a very short introduction - Passingham, R. E. 1943- (Oxford, United Kingdom Oxford University Press, 2016)
In this Very Short Introduction Richard Passingham, a distinguished cognitive neuroscientist, gives a provocative and exciting account of the nature and scope of this relatively new field, and the techniques available to us, focusing on investigation of the human brain. He explains what brain imaging shows, pointing out common misconceptions, and gives a brief overview of the different aspects of human cognition: perceiving, attending, remembering, reasoning, deciding, and acting. Passingham concludes with a discussion of the exciting advances that may lie ahead.
A recent field -- Perceiving -- Attending -- Remembering -- Reasoning -- Deciding -- Checking -- Acting -- The future.
Includes bibliographical references (pages 111-125) and index.
Keywords: Cognitive neuroscience